Antibiotic Susceptibility Profile and Beta Lactamase Production of Staphylococcus aureus Isolated from Mobile Phones of Students from College of Natural and Pharmaceutical Sciences, Bayero University Kano, Nigeria - Bala, H. K.; Murtala, Z.; Bala R. K. (UMYU Journal of Microbiology Research)
Study’s Excerpt: